IV Meeting of formative research (VITAL, 2025)
On November 8, the IV Meeting of formative research was held with the participation of teachers, researchers and students of the research line of study. During the activity, the results of various research projects in areas such as epidemiology, pharmacology, molecular biology, mental health and tissue engineering, among others, were shown.
Keywords: Formative research; Clinical studies; Epidemiology; Pharmacology; Molecular biology